The Red-Ink Grant: Tracing Legitimacy in History - Mobarak Ali, Bashiran Begum (Journal of Malaysian and Comparative Law, 2007)
The most unusual feature of the Federal Constitution, according to Harding, is the way it entrenches special rights and privileges reserved to a racially defined group of the Malaysian population, namely the Malays. The special rights and privileges of the Malays constituted the central and most sensitive issue in the formation of Malaysia, and their adoption into the Constitution was justified by the fact that the Malays were, although numerically in the majority, a historically disadvantaged race. This article aims at scrutinising the extent to which the Malays claim on land is protected and preserved in Malaysian law. The focal point of the discussion is Wan Sulaiman FJ's statement in the Collector of Land Revenue v Noor Cahaya where he characterised the Malay Reservation Land as a "Cinderella piece of property". This article explores the issue of reservation policy from a legal and historical perspective and addresses the following questions: How did the Malay Reservation Land come about in Malaysia? Who introduced this policy? And what were the reasons for this policy?